PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD TERHADAP HASIL BELAJAR KOGNITIF, MOTIVASI, DAN AKTIVITAS BELAJAR SISWA PADA KONSEP EKOSISTEM DI MTSN MODEL BANDA ACEH - Nurmahni Harahap (Jurnal Visipena, 2013)
This research was aimed to know the differences of cognitive learning outcomes, motivation, student learning activity in the implementation of cooperative learning model of STAD type and conventional learning, and the relation between motivation and student learning activity towards cognitive learning outcomes in the implementation of cooperative learning model of STAD type. The method in this research used was quasi experiment. The population in this research was all of seventh grade students of MTsN Model Banda Aceh totaling 396 students from 11 classrooms. Sampling was done with random sampling technique. The research instrument was used cognitive learning outcomes test, student motivation questionnaire, and observation sheet student learning activity. Data analysis was used t test and multiple correlation test at significance level of 0.05. The cognitive learning outcomes obtained tcount = 2.18. Students motivation obtained tcount = 4.05. Student learning activity obtained tcount = 17.25. This means there are the differences of cognitive learning outcomes, student motivation, student learning activity in both classes. The relation between motivation and student learning activity towards cognitive learning outcomes obtained R = 0.56 which means it has enough relation. The conclusion of this research is there are differences in cognitive learning outcomes, motivation, of student learning activity in the implementation of cooperative learning model of STAD type and conventional learning, and there is a relation between motivation and student learning activity towards cognitive learning outcomes in the implementation of cooperative learning model STAD type. As an effort to improve cognitive learning outcomes, motivation and of student learning activity optimally, it is expected that biology teachers can apply the cooperative learning model of STAD type that anable students to engage actively in the learning process.